The determinants of optimal capital structure : an empirical investigation of Malaysian construction (property) companies - Samaon @ Samson, Entebang (Universiti Malaysia Sarawak (UNIMAS), 2002)
The focus of this research paper is to study the determinant of optimal capital structure of 51 Construction companies (27 from Main Board and 24 from Second Board) quoted on the Kuala Lumpur Stock Exchange. The panel data was extracted from the three years audited accounts from 1998 to 2000 from each of the company under study